Text readability: its impact on reading comprehension and reading time - Zainurrahman, Zainurrahman; Yusuf, Fazri Nur; Sukyadi, Didi (Journal of Education and Learning (EduLearn), 2024)
Recently, the readability of texts has become the focus of reading research because it is believed to have implications for reading comprehension, which is of utmost importance in the field of English as a foreign language (EFL), particularly in the teaching, learning and assessment of reading comprehension. Unfortunately, the influence of text readability on reading comprehension (and reading time) has not been well studied in the EFL context. Most text readability studies are conducted in medical contexts, but these studies are often limited in predicting readability scores for sample texts. To address this gap, the current study aimed to evaluate the influence of text readability levels (based on the Flesch-Kincaid grade level (FKGL)) on students’ reading comprehension and reading time. Data were collected through reading test and analyzed using SPSS version 22. The Friedman test revealed that the distribution of students' reading comprehension score (X2=197.532, p=0.000) and reading time (X2=215.323, p=0.000) are different in each text, suggesting that the readability of texts has a significant influence on both. This study contributed to the practices of reading instruction and assessment. Limitations and suggestions for further research are briefly discussed.